Keakuratan Claude Dalam Mengidentifikasi Kedudukan Dan I'râb Studi Komparatif Dengan Kitab Syarh Al-Kafrâwî - Surya Saputra, Yoni; Ghofur, Abdul (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2025)
This study aims to analyze the accuracy of Claude 3.0 in determining i'râb and i'rabbing Arabic texts using al-Âjurrûmiyyah book and comparing the results using Syarh al-Kafrâwî book.  The research method used was descriptive qualitative comparative. Primary data is in the form of analysis of Claude 3.0 results, while secondary data comes from the book of Syarh al-Kafrâwî. Data collection techniques were conducted through documentation, systematic observation, and triangulation analysis. The results showed that the accuracy of Claude 3.0 increased with the use of more detailed prompts. However, errors in i'rab identification remain, especially in words with high characteristics and complexity. Errors were also found in the determination of word status and i'rab signs. The platform shows potential to support Arabic grammar learning, but it is not yet able to match traditional methods or manual analysis in its entirety. The limitations of the study lie in the complexity of the text and the Claude 3.0 algorithm which is not fully compliant with nahwu rules. Nevertheless, this study contributes to developing the utilisation of AI for Arabic language education.